Strategi Komunikasi Pemasaran Catering Zella dalam Mempertahankan Loyalitas Pelanggan Selama COVID-19 - Arvin Stephensius; Septia Winduwati (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Catering Zella is one of the MSMEs which is engaged in the food business. This UMKM has become one of the popular caterers in Bekasi City. However, since the COVID-19 virus entered Indonesia and the stipulation of the PSBB by the government, Catering Zella has experienced a decline in turnover. But Catering Zella was able to survive. The success in surviving these difficult times cannot be separated from the communication strategy adopted by Catering Zella. By using qualitative research types and case study research methods, the author wants to describe how the communication strategy adopted by Catering Zella in maintaining customer loyalty during the COVID-19 pandemic. The purpose of this study was to determine the marketing communication strategy in maintaining customer loyalty of Catering Zella during the COVID-19 pandemic. The theories used in this research are marketing communication strategy theory, UMKM, and customer loyalty. The data analyzed were the results of interviews with a permanent lecturer at the Faculty of Communication Sciences at Tarumanagara University, literature studies related to communication strategies and customer loyalty, as well as a review of documents related to Zella Catering. The results of this study indicate that Catering Zella is able to maintain customer loyalty through a marketing communication strategyCatering Zella merupakan salah satu UMKM yang bergerak dalam bidang usaha makanan. UMKM ini menjadi salah satu catering yang diminati di Kota Bekasi. Namun, sejak virus COVID-19 masuk ke Indonesia dan ditetapkannya PSBB oleh pemerintah, Catering Zella mengalami penurunan omset. Namun Catering Zella mampu bertahan. Kesuksesan untuk bertahan di masa-masa sulit ini tentu tidak lepas dari strategi komunikasi yang diterapkan oleh Catering Zella. Dengan menggunakan jenis penelitian kualitatif dan metode penelitian studi kasus, penulis ingin menguraikan bagaimana strategi komunikasi yang diterapkan oleh Catering Zella dalam mempertahankan loyalitas pelanggan selama pandemi COVID-19. Tujuan penelitian ini adalah untuk mengetahui strategi komununikasi pemasaran dalam mempertahankan loyalitas pelanggan Catering Zella selama pandemi COVID-19. Teori-teori yang digunakan dalam penelitian ini adalah teori strategi komunikasi pemasaran, UMKM, dan loyalitas pelanggan. Data yang dianalisis merupakan hasil wawancara dengan satu dosen tetap Fakultas Ilmu Komunikasi Universitas Tarumanagara, studi kepustakaan yang berkaitan dengan strategi komunikasi dan loyalitas pelanggan, serta telaah dokumen yang berkaitan dengan Catering Zella. Hasil penelitian ini menunjukkan bahwa Catering Zella mampu mempertahankan loyalitas pelanggannya melalui strategi komunikasi pemasaran